"Bright spotty lesions" on spinal magnetic resonance imaging differentiate neuromyelitis optica from multiple sclerosis. (March 2014) - Yonezu, Tadahiro; Ito, Shoichi; Mori, Masahiro; Ogawa, Yoshitsugu; Makino, Takahiro; Uzawa, Akiyuki; Kuwabara, Satoshi
Background: Spinal magnetic resonance imaging (MRI) finding of longitudinally extensive spinal cord lesions (LESCL) extending over three vertebral segments and involvements of spinal central gray matter have been reported in patients with neuromyelitis optica (NMO). Objectives: We aimed to review spinal MRI findings in NMO and multiple sclerosis (MS), and to determine whether the "bright spotty lesions" (BSLs) are a discriminative finding of NMO. Methods: For this study, 24 consecutive patients with NMO and 34 patients with MS were enrolled. BSLs were defined as very hyperintense spotty lesions on axial T2WI. We also studied the length, distribution, signal homogeneity, size, and presence of contrast-enhanced lesions. Results: BSLs were more frequently found in patients with NMO (54%) than in those with MS (3%; p < 0.01). LESCL were found in 67% of the NMO patients. BSLs were seen in 63% of the patients without LESCL. BSLs or LESCL were found in 88% of the NMO patients. Inhomogeneous lesions, transversally extensive lesions, and central lesions were more frequently seen in NMO than in MS. Conclusions: BSLs are a newly defined spinal MRI finding specifically seen in NMO. In combination with LESCL, BSLs can help differentiate patients with NMO from those with MS with higher sensitivity than LESCL alone.